The complete mitochondrial genome of Astatotilapia burtoni. (3rd July 2016) - Hu, Xiao-Xiao; Lu, Jiang; He, Shi-Yang; Li, Xiang-Feng; Liu, Hong-Jie; Han, Li-Juan
Abstract: Astatotilapia burtoni is a species of fish in the Cichlidae family. Astatotilapia burtoni has been used as a model organism to research the behaviors and physical systems of cichlids. Here, we reported the complete mitogenome sequence of A. burtoni, which was 16, 583 bp and composed of 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes and 1 control region, with a base composition of lower G + C content (45.5%). Similar to Astatotilapia calliptera, all genes were located on H-strand except for eight tRNAs and ND6 genes. Most protein-coding genes started with an ATG codon except for COX1, ATP6 and ND3, which initiated with GTG or ATC instead, and terminated with the typical stop condon (TAA/TAG)or a single T. In this article, 12 protein-coding genes of other 10 closely species were used to construct the species phylogenetic tree to convince the mitogenome sequences. These results provided basic information for researching A. burtoni on genetics, phylogeny and adaptive evolution.